2022
DOI: 10.3390/jcm11061740
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiomics in the Era of Immune Checkpoint Inhibitors: A New Protagonist in the Jungle of Response Criteria

Abstract: Immune checkpoint inhibitors (ICI) have demonstrated encouraging results in terms of durable clinical benefit and survival in several malignancies. Nevertheless, the search to identify an “ideal” biomarker for predicting response to ICI is still far from over. Radiomics is a new translational field of study aiming to extract, by dedicated software, several features from a given medical image, ranging from intensity distribution and spatial heterogeneity to higher-order statistical parameters. Based on these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…35 In addition, Radiomics features could be utilized as a digital biopsy, an alternative or supplement to surgical biopsy specimens, 36 as generally, obtaining imaging of patients is a nonaggressive and relatively inexpensive surveying method, and the option of performing multiple imaging studies in time series may better enable clinicians to enroll suitable patients for appropriate treatments. 21 Although our results are promising, they should be viewed in light of several limitations. First, the anatomical variations in different cancers from different organs may affect the parameters of the tumor periphery.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…35 In addition, Radiomics features could be utilized as a digital biopsy, an alternative or supplement to surgical biopsy specimens, 36 as generally, obtaining imaging of patients is a nonaggressive and relatively inexpensive surveying method, and the option of performing multiple imaging studies in time series may better enable clinicians to enroll suitable patients for appropriate treatments. 21 Although our results are promising, they should be viewed in light of several limitations. First, the anatomical variations in different cancers from different organs may affect the parameters of the tumor periphery.…”
Section: Discussionmentioning
confidence: 82%
“…However, some counteroffensive strategies emerge in a subset of malignancies, such as the expression of PD‐L1 and B7‐1/B7‐2 on the surface of tumor cells, which interact with T cells and inhibit their function and survival 20 . Previous studies have investigated the potential of radiomics features for predicting tumor response to immune checkpoint inhibitors, small molecule drugs specifically crafted to alter the tumor‐immune cell interaction, 21 determining PD‐L1 expression in malignant tissue, 22 and also classifying tumors from single histopathologies with different degrees of invasiveness 23 . Lo Gullo et al showed that a combination of five radiomics features could determine the status of PD‐L1 expression with a sensitivity of 90.7% and specificity of 85.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, clinicians need a reliable and standardized imaging method, to better assess therapy response, similarly to what happens in other neoplasms [8,9]. Despite auspicious premises, [18F]F-choline PET is not currently recommended for the evaluation of response to therapy assessment in PCa, mainly due to the lack of large-scale prospective trials [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the combination of metabolic information on PET with other clinical and laboratory data can provide useful information in various therapeutic regimens, including checkpoint inhibitors, particularly in tumors such as melanomas and non-small cell lung cancer (NSCLC) [ 7 ]. To better cover the argument, two dedicated reviews [ 9 , 10 ] and two original articles [ 9 , 10 ] have been provided describing the impact of [ 18 F]FDG PET/CT at different timing in both abovementioned tumors. Liberini and colleagues [ 11 ] investigated patients with advanced melanoma undergoing target therapy or immunotherapy and correlated baseline information on PET with tumor response, PFS and OS, proving that poorer outcome was correlated to higher values of whole-body and bone metabolic parameters, whereas OS was correlated to higher values of whole-body, lymph node, and soft tissue metabolic parameters.…”
mentioning
confidence: 99%
“…With regard to imaging, much progress has been made, but also much more remains to be achieved. To help better understand the topic, a dedicated article has been prepared by Castello and colleagues [ 10 ], providing a comprehensive review on radiomics in the era of ICI as a new protagonist in the “jungle” of response criteria. By means of this article [ 10 ], together with the last contribution [ 9 ], the Special Issue has been complemented with up-to-date knowledge on advanced metabolic imaging in cancer patients candidate to immunotherapy.…”
mentioning
confidence: 99%